CHARACTERIZATION OF CARBOXY METHYL CELLULOSE (CMC) FROM Eichornia crassipes (Mart) Solms - Arum Wijayani; Khoirul Ummah; Siti Tjahjani (Indonesian Journal of Chemistry, 2005)
Carboxy Methyl Cellulose (CMC), a compound made made of eceng gondok has been implied for its characteristic by a constructive wet system, with media such as methanol, propanol and water. Four consecutive phases involving alkalization, carboxymethylization, neutralization and drainage were used in the making process of CMC. The first two process were prepared by reacting NaOH and ClCH2COONa with NaOH 22; 32.5; 39.2; 45.9 g and 20; 26; 32; 38 g ClCH2COONa respectively. Added acetic acid was used in the neutralization process, whilst drainage only involved heating in the oven. The overall result for each characteristic substitution degree, acidity; viscosity; contens of water consentration of NaCl and purity 0.4 - 0.85, 6.10 - 8.49, 3 - 10 cP, 3.57 - 19.4 %, 12.9 - 22.4 % and 77.96 - 87.09 % respectively. Based on the obtained characteristic, could be concluded that CMC is considered as a technical quality and can also be used as filler constituent in adhesive.